The woman's Qura'nic Discourse in Grammatical Coherence - عبدالله ظاهر, أحمد (Journal of College of Education, 2021)
This current paper reveals that the Qura'nic discourse is an inclusive and not limited to verbal dimension alone neither social nor historic even the pragmatics in a certain position, but it combines among these dimensions theoretically and practically. The current paper has reveled one of the characteristics of this discourse which is the grammatical cohesion , that is considered a grammatical characteristic for discourse and relied on the sentences relation to each other. It is almost created through tools that appeared in the text directly as generative pronouns, conjunctions and repetition.